Elastic adhesive bandage in low back pain in active and sedentary pregnant women living in Coari, Amazonas - Fernandes, Emanuela Moraes Silva; Matos, Gabrielle Silveira Rocha; Andrade, Ercília de Souza; Nunes, Cleuzenir Melo; Matos, Maria Luciana Moura de; Maciel, Thiago dos Santos (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Gestational low back pain is a limiting symptom, which interferes in the activities of daily living and quality of life. There are several scientific findings on the effectiveness and benefits of banding for low back pain, making it necessary to investigate effective and inexpensive non-pharmacological technologies. Objectives: The objective of this study was to compare the effect of elastic adhesive bandage (EAB) in low back pain in active and sedentary pregnant women. Method: Study quasi-experimental, analytical with 33 pregnant women living in the city of Coari (AM). Socio-demographic, obstetrical data on health and low back pain were collected. The bandage was applied like “I”, with two bands in the paravertebral region of the lumbar spine and should remain for 3 days. Pain intensity was assessed by visual analogue pain scale (VAS) during the initial evaluation and after 3 days of the application procedure. For purposes of analysis, the sample was divided into 2 groups: active and sedentary. The Wilcoxon test was used to compare the mean of the low back pain intensity before and after the application of the intra-group bandage. The mean intensity of low back pain after the application of bandaging between groups was analyzed by the Mann-Whitney U test. Significance was accepted for p≤0,05. Results: The mean age was 24.24 (±6.39) and 75.8% reported low back pain at moderate intensity. The pain intensity after application of the EAB was lower in both the active (p=0.039) and the sedentary (p=0.000). There was no difference in pain intensity on day 3 in intragroup analysis (p=0.691). Conclusion: EAB reduced the intensity of low back pain in both active and sedentary pregnant women, however, there was no difference in its effect when the groups were compared.